2022
DOI: 10.1002/pon.6069
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial functioning of parents of Dutch long‐term survivors of childhood cancer

Abstract: Objective: To describe health-related quality of life (HRQoL), post-traumatic stress and post-traumatic growth of parents of long-term survivors of childhood cancer (CCS) and study associated factors. Methods: Parents of survivors of the Dutch Childhood Cancer Survivor Study LATER cohort below 30 years and diagnosed 1986-2001 were invited to complete the TNO-AZL Questionnaire for Adult's HRQoL (e.g., sleep and aggressive emotions), Self-Rating Scale for Post-traumatic Stress Disorder, Post-traumatic Growth Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…Concerning cancer‐related factors, we expected higher risk for siblings of CCS with CNS tumors, because of worse outcomes for CCS with CNS themselves. However, having a child with a CNS tumor was also not related to psychosocial functioning in parents of long‐term CCS 34 . Apart from an association of small to medium size between siblings of CNS CCS and pain, we found no associations between the outcomes and cancer‐related factors, which is substantiated in literature 8,11,35 …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Concerning cancer‐related factors, we expected higher risk for siblings of CCS with CNS tumors, because of worse outcomes for CCS with CNS themselves. However, having a child with a CNS tumor was also not related to psychosocial functioning in parents of long‐term CCS 34 . Apart from an association of small to medium size between siblings of CNS CCS and pain, we found no associations between the outcomes and cancer‐related factors, which is substantiated in literature 8,11,35 …”
Section: Discussionsupporting
confidence: 82%
“…However, having a child with a CNS tumor was also not related to psychosocial functioning in parents of long-term CCS. 34 Apart from an association of small to medium size between siblings of CNS CCS and pain, we found no associations between the outcomes and cancer-related factors, which is substantiated in literature. 8,11,35 Following these results, factors that impact long-term psychosocial functioning of siblings of CCS might not differ from factors that impact the functioning of the general population.…”
Section: Associated Factorssupporting
confidence: 83%
See 1 more Smart Citation
“…Although the dominant narrative around 'thinking positively' is not always helpful for cancer patients and their families as they go through treatment, 31 our data echoes other international studies in 32 and a recent study among CCSparents showed PTG associated with better health-related quality of life. 12 With parents expressing a wish for more psychological support, 33 mental health professionals can harness follow-up appointments as opportunities to engage people in envisioning their futures in concrete, adaptive ways to maximize their personal development. [34][35][36]…”
Section: Discussionmentioning
confidence: 99%
“…To date, most studies have assessed PTG in CCS‐parents shortly after treatment completion, and there is very limited evidence on how parents fare in the long‐term, decades after their child's illness (≥20 years) 12 . There is also a lack of research on PTG in the general population.…”
Section: Introductionmentioning
confidence: 99%